3D particle models for composite laminates with anisotropic elasticity. (15th September 2018) - Wan, Lei; Yang, Dongmin; Ismail, Yaser; Sheng, Yong
Abstract: This paper presents an assessment of three different particle based approaches for 3D modelling of fibre reinforced polymer (FRP) composite laminates with anisotropic elasticity, namely 3D Discrete Lattice model, 3D Hexagonal Close Packing model and Extended 2D Hexagonal and Square Packing model. These approaches are compared and evaluated against experimental results using a 0 ∘ ply lamina case. It has been confirmed that the Extended 2D Hexagonal and Square modelling approach in Discrete Element Method (DEM) is capable of modelling 3D composite laminates with better efficiency. Angle-ply lamina and two different laminates are modelled with the chosen particle approach. Good agreements between DEM, Finite Element and theoretical results prove the capability of this developed DEM approach for modelling the elastic behaviour of general FRP composite lamina and laminates.